The Turkish League Against Rheumatism Recommendations for the Management of Hand Osteoarthritis Under Guidance of the Current Literature and 2018 European League Against Rheumatism Recommendations - Fikriye Figen AYHAN,; İsmihan SUNAR,; Ebru UMAY,; Dilek KESKİN,; Lale ALTAN,; Fitnat DİNÇER,; Tuncay DURUÖZ,; Nazım KARALEZLİ,; Banu KURAN,; Tiraje TUNCER, (Archives of Rheumatology, 2020)
Objectives: This study aims to explore the accordance to the 2018 European League Against Rheumatism (EULAR) recommendations for the management of hand osteoarthritis (OA) among the Turkish League Against Rheumatism (TLAR) expert panel and composition of TLAR recommendations for the management of hand OA under guidance of the current literature. Materials and methods: The TLAR convener designated an expert panel of 10 physicians experienced in hand OA for this process. The 2018 EULAR recommendations for the management of hand OA and the systematic review of the literature were sent to the expert panel via e-mails. The e-mail process which included Delphi round surveys was completed. The EULAR standard operational procedure Appraisal of Guidelines for Research and Evaluation II was followed. The level of agreement was calculated for each item and presented as mean, standard deviations, minimum and maximum and comparisons of 2018 EULAR recommendations were performed. Results: Five overarching principles and 10 recommendations were discussed. Revisions were held for the sixth, seventh, and ninth recommendations with lowest level of agreements. These recommendations were revised in accordance with suggestions from the experts and re-voted. The revised forms were approved despite the lack of statistically significant difference between these forms (p=0.400, p=0.451, p=0.496, respectively). Except for the ninth recommendation about surgery (p=0.008), no significant difference in level of agreements was observed between the EULAR and TLAR hand OA recommendations. The 11th recommendation about paraffin bath was added. Conclusion: The optimal treatment of hand OA consists of personalized non-pharmacological (self-management, exercise, splint), pharmacological (topical non-steroidal anti-inflammatory drugs as the first choice), and interventional procedures (only for refractory cases) based on shared decision between the patient and physician. TLAR hand OA recommendations were created mainly based on the most recent literature and the last EULAR hand OA management recommendations, which are widely approved among the TLAR experts.